Diaphragm adhesive tape and preparation method thereof
By using an acrylate polymer with a specific molecular structure to composite with a polyolefin coating in the separator tape, the problems of easy dissolution of the separator tape in the electrolyte and low metal ion permeability are solved, achieving higher bonding strength and interface stability, and improving the cycle performance and safety of the battery.
Patent Information
- Application Number
- CN202512041905.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-03-20
AI Technical Summary
Existing separator tapes are prone to dissolving and falling off in electrolytes, leading to electrode cracking and low metal ion permeability, which affects the cycle performance and safety of the battery.
An acrylate polymer with a specific molecular structure is composited with a polyolefin coating to form a functional layer and an adhesive layer, which enhances interfacial compatibility and bonding strength, and improves electrolyte wetting ability and metal ion migration efficiency.
It improves the bonding strength and interfacial stability of the separator tape in the electrolyte, suppresses the risk of metal precipitation at the bending corners of the electrode, and enhances the cycle performance and safety of the battery.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention belongs to the field of diaphragm tape, and particularly relates to a diaphragm tape and its preparation method. Background Technology
[0002] In the battery manufacturing process, the positive electrode, negative electrode, and separator typically undergo multiple critical processes such as hot pressing, liquid injection, and formation before being packaged into a battery cell. However, the inner layer of the battery cell has bending stress at the corners, which makes it prone to cracking and detachment after hot pressing. At the same time, the cracked corners pose a risk of internal short circuit failure, affecting the yield rate and safety of the battery cell.
[0003] Currently, the industry commonly attempts to apply specialized separator tape to the edges, ends, or bending areas of the electrode sheets to alleviate stress concentration, thereby preventing electrode cracking and suppressing problems such as metal deposition, deformation, or breakage at corners caused by deformation during battery cycling. However, conventional separator tapes often experience problems such as adhesive layer dissolution and peeling after contact with electrolyte, rendering them ineffective. While some separator tapes using electrolyte-resistant adhesives can resist electrolyte corrosion, their overly dense adhesive layers often result in low metal ion permeability, hindering metal ion migration and leading to uneven local current distribution. This, in turn, can cause metal deposition, affecting the battery's cycle performance.
[0004] Therefore, given the current trend of batteries moving towards higher energy density, higher cycle stability, and higher safety requirements, there is an urgent need to develop a separator tape that can effectively protect the electrode structure and prevent metal precipitation during long-term cycling. Summary of the Invention
[0005] To improve the electrolyte resistance and metal ion permeability of diaphragm tape, this invention provides a diaphragm tape and its preparation method.
[0006] According to one aspect of the present invention, a diaphragm tape is provided, the diaphragm tape comprising a functional layer and an adhesive layer; the functional layer comprising a polyolefin coating, the adhesive layer being disposed on the surface of the polyolefin coating; wherein the adhesive layer comprises an acrylate polymer, the structural formula of which is shown in formula (I); Formula (I) In formula (I), R1 is at least one of methyl, ethyl, butyl, isooctyl, isononyl, and lauryl; R2 is at least one of methyl, ethyl, butyl, and isobutyl; R3 and R4 are hydrogen atoms and / or methyl; R5 is a substituted ethyl or propyl group; and a≥1, b≥1, c≥0, d≥1, e≥1; The number-average molecular weight of the acrylate polymer is 100,000 g / mol to 150,000 g / mol.
[0007] The inventors discovered through research that when ordinary acrylate polymers are directly laminated with polyolefin coatings, the large difference in polarity can easily lead to poor interfacial compatibility, resulting in insufficient adhesion between the adhesive layer and the substrate, interfacial delamination, or localized peeling. In this invention, by selecting acrylate polymers with specific molecular structures to laminate with polyolefin coatings, not only is the overall adhesion strength and interfacial stability of the separator tape in the electrolyte significantly improved, but the wetting ability and distribution uniformity of the electrolyte on the tape surface are also significantly enhanced. This, in turn, improves the migration efficiency of ions during electrocycling and effectively suppresses the risk of metal deposition at the bending edges of the electrodes.
[0008] Preferably, the thickness of the polyolefin coating is 0.2 μm to 2 μm.
[0009] Preferably, the functional layer further includes a base film layer.
[0010] Preferably, a polyolefin coating is disposed on at least one surface of the base film layer.
[0011] Preferably, the base film layer is at least one of polypropylene (PP), polyethylene (PE), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and nonwoven fabric.
[0012] Preferably, the porosity of the base film layer is 30% to 85%.
[0013] Preferably, the air permeability of the functional layer is 10s / 100cc to 350s / 100cc.
[0014] Preferably, the adhesive layer is discontinuously distributed on the functional layer.
[0015] Preferably, the area of the adhesive layer accounts for 15% to 35% of the total area of the functional layers. Furthermore, by controlling the formed composite structure, not only can the permeability of the diaphragm tape be improved, but the adhesion of the adhesive layer to the functional layers can also be enhanced.
[0016] Preferably, the adhesive layer is distributed on the surface of the functional layer in any one of the following ways: dotted, blocky, or linear.
[0017] Preferably, the raw materials for preparing the acrylate polymer include soft monomers, hard monomers, and functional monomers; wherein the homopolymer of the soft monomers has a glass transition temperature of T. g1 T g1 ≤ 10℃; the glass transition temperature of homopolymers of hard monomers is T g2 T g2 ≥ 20℃; the glass transition temperature of the homopolymer of the functional monomer is T g3 -20℃≤ T g3 ≤ 140℃.
[0018] Preferably, both the soft monomer and the hard monomer are acrylate monomers.
[0019] Preferably, the soft monomer includes at least one of methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, isononyl acrylate, and lauryl acrylate.
[0020] Preferably, the hard monomer includes at least two of methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobornyl methacrylate, and vinyl acetate.
[0021] Preferably, the functional monomer includes an acrylic monomer and a hydroxyl-containing acrylate monomer. The acrylic monomer is at least one selected from acrylic acid and methacrylic acid; the hydroxyl-containing acrylate monomer is at least one selected from hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate.
[0022] Preferably, the ratio of soft monomer to hard monomer to functional monomer is calculated by mass ratio as 50~70:13~40:10~17.
[0023] Preferably, the mass ratio of acrylic monomer to hydroxyl-containing acrylate monomer is 0.5~2:10~5.
[0024] Preferably, the raw materials for preparing the acrylate polymer also include an initiator, which includes at least one selected from azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide. The amount of initiator used is 0.05% to 0.5% of the total mass of the soft monomer, hard monomer, and functional monomer.
[0025] Preferably, the acrylate polymer is prepared by adding a mixture of soft monomers, hard monomers, functional monomers and solvents in batches to a solution containing an initiator and reacting at 55-75°C for 2-4 hours.
[0026] Preferably, the raw materials for preparing acrylate polymers also include a solvent, which includes at least one of toluene, acetone, and ethyl acetate.
[0027] Preferably, the solid content of the acrylate polymer solution is 38% to 45%.
[0028] Preferably, the polyolefin coating is prepared by drying a polyolefin emulsion; the polyolefin emulsion is prepared by solution emulsification or melt emulsification. By using a polyolefin emulsion to prepare the polyolefin coating, the polyolefin coating can further enhance the mechanical structural strength and needle puncture resistance of the diaphragm tape while maintaining the required air permeability of the diaphragm, which helps to reduce the probability of short circuits.
[0029] Solution emulsification involves dissolving polyolefins in an organic solvent to form a polymer solution. Then, while mechanically stirring the polymer solution, solvent is added along with some emulsifiers and related additives. After high-pressure homogenization or extremely high-shear emulsification, the solvent in the system is finally distilled to obtain a polyolefin emulsion. Melt emulsification involves heating the polyolefin and emulsifier to a molten state, then adding solvent while stirring and emulsifying to obtain a polyolefin emulsion.
[0030] Preferably, the polyolefin emulsion includes a modified polyolefin resin.
[0031] Preferably, the modified polyolefin resin is prepared by reacting a polyolefin with a modifier; wherein the polyolefin includes at least one of styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), hydrogenated styrene-ethylene-propylene-styrene block copolymer (SEPS), polypropylene (PP), polyethylene (PE), and ethylene-vinyl acetate copolymer (EVA); and the modifier includes at least one of maleic anhydride, acrylic acid, and acrylate.
[0032] Preferably, the modified polyolefin resin is a blend of maleic anhydride-grafted polypropylene and maleic anhydride-grafted SEBS, with a mass ratio of maleic anhydride-grafted polypropylene to maleic anhydride-grafted SEBS of 1 to 4:1.
[0033] Preferably, the polyolefin emulsion also includes an emulsifier and a solvent.
[0034] Preferably, the solid content of the polyolefin emulsion is 10% to 25%.
[0035] Preferably, the viscosity of the polyolefin emulsion is 10 mPa·s to 200 mPa·s.
[0036] Preferably, the emulsifier includes anionic emulsifiers and nonionic emulsifiers, wherein the anionic emulsifier is an alkyl sulfonate emulsifier or an alkyl sulfate emulsifier.
[0037] Preferably, the alkyl sulfonate emulsifier is selected from one or more of sodium dodecylbenzene sulfonate, sodium dioctyl succinate sulfonate, sodium dodecyl sulfonate, and sodium α-olefin sulfonate.
[0038] Preferably, the alkyl sulfate emulsifier is selected from one or more of sodium dodecyl sulfate and sodium fatty alcohol polyoxyethylene ether sulfate.
[0039] Preferably, the nonionic emulsifier is selected from one or more of polyvinylpyrrolidone, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan monooleate.
[0040] Preferably, the solvent includes at least one of water, ethanol, acetonitrile, ethyl acetate, isopropanol, n-butanol, n-hexane, cyclohexane, petroleum ether, benzene, toluene, dimethylformamide, dimethylacetamide, and ethyl acetoacetate.
[0041] In another aspect, the present invention provides a method for preparing the diaphragm tape as described above, the method comprising the following steps: S1. Preparing a functional layer and an adhesive layer respectively: applying an acrylic polymer adhesive solution to the surface of a release film and drying it to obtain an adhesive layer; applying a polyolefin emulsion to the surface of a base film layer and drying it to obtain a functional layer; S2. After the adhesive layer is bonded to the polyolefin coating surface of the functional layer, the diaphragm tape is obtained after high-temperature curing.
[0042] Preferably, the high-temperature curing process is carried out at a temperature of 50°C to 60°C for 24 to 48 hours.
[0043] The beneficial effects of this invention are as follows: In separator tapes, the composite of acrylate polymers and polyolefin coatings may suffer from reduced interfacial compatibility due to polarity differences, which could affect the adhesion performance between the adhesive layer and the substrate. This invention, by selecting acrylate polymers with specific molecular structure designs to composite with polyolefin coatings, not only helps improve interfacial compatibility, thereby enhancing the tape's adhesion strength and interfacial stability in the electrolyte, but also enhances the wetting ability and uniform distribution of the electrolyte on the tape surface. This promotes the migration efficiency of ions during electrocycling, which helps suppress the risk of metal deposition at the bending edges of the electrodes. Detailed Implementation
[0044] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0045] Example 1 1. Prepare the raw materials needed for the diaphragm tape. According to the formula shown in Table 1, weigh the raw materials required for preparing the diaphragm tape. Among them, the PP diaphragm used in the base membrane layer was purchased from Henan Tiangong PPH-16, with an air permeability of 180s / 100cc and a thickness of 16μm; the polyolefin emulsion was prepared by adding solvent and emulsifier to the melt of polyolefin resin and subjecting it to high-speed shearing and distillation, with a solid content of 20% and a viscosity of 100mPa·s; the acrylate polymer was prepared by adding a mixture of soft monomers, hard monomers, functional monomers and solvents in batches to a solution containing an initiator and reacting at 65℃ for 3 hours.
[0046] Table 1. Raw materials required for diaphragm tape
[0047] 2. Preparation of diaphragm tape S1. Preparation of the functional layer and adhesive layer: An acrylate polymer is coated onto the surface of a release film, and after drying, a discontinuous adhesive layer is obtained; a polyolefin emulsion is coated onto the surface of a base film layer, and after drying, a functional layer is obtained; wherein, the thickness of the adhesive layer is 2 μm, and the thickness of the polyolefin coating is 1 μm; in this embodiment, the adhesive layer is distributed in a dotted pattern on the surface of the functional layer (the diameter of the dots is 200 μm), and the area of the adhesive layer accounts for 20% of the total area of the functional layer; S2. The adhesive layer and the polyolefin coating surface of the functional layer are bonded together (transfer coating) and wound up, and then cured at 60°C for more than 24 hours to obtain the diaphragm tape.
[0048] Example 2 This embodiment refers to the formula and method provided in Embodiment 1 to prepare diaphragm tape. The difference from Embodiment 1 is that in this embodiment, the area of the adhesive layer accounts for 15% of the total area of the functional layer when preparing the diaphragm tape. Apart from the above differences, the operation steps for preparing the diaphragm tape in this embodiment are strictly consistent with those in Embodiment 1.
[0049] Example 3 This embodiment refers to the formula and method provided in Embodiment 1 to prepare diaphragm tape. The difference from Embodiment 1 is that in this embodiment, the area of the adhesive layer accounts for 35% of the total area of the functional layer when preparing the diaphragm tape. Apart from the above differences, the operation steps for preparing the diaphragm tape in this embodiment are strictly consistent with those in Embodiment 1.
[0050] Example 4 This embodiment refers to the formulation and method provided in Example 1 to prepare diaphragm tape. The difference from Example 1 is that the formulation of the acrylate polymer used in the adhesive layer prepared in this embodiment is shown in Table 2. Apart from the above differences, the operation steps for preparing diaphragm tape in this embodiment are strictly consistent with those in Example 1.
[0051] Table 2. Raw materials required for diaphragm tape
[0052] Example 5 This embodiment refers to the formulation and method provided in Example 1 to prepare diaphragm tape. The difference from Example 1 is that the formulation of the acrylate polymer used in the adhesive layer prepared in this embodiment is shown in Table 3. Apart from the above differences, the operation steps for preparing diaphragm tape in this embodiment are strictly consistent with those in Example 1.
[0053] Table 3. Raw materials required for diaphragm tape
[0054] Example 6 This embodiment prepares diaphragm tape with reference to the formulation and method provided in Example 1. The difference from Example 1 is that the formulation of the acrylate polymer used in the adhesive layer prepared in this embodiment is shown in Table 4. Apart from the above differences, the operation steps for preparing diaphragm tape in this embodiment are strictly consistent with those in Example 1.
[0055] Table 4. Raw materials required for diaphragm tape
[0056] Example 7 This embodiment refers to the formulation and method provided in Example 1 to prepare diaphragm tape. The difference from Example 1 is that in preparing the functional layer of the diaphragm tape in this embodiment, the modified polyolefin resin used is a blend of maleic anhydride-grafted polypropylene and maleic anhydride-grafted SEBS, with a mass ratio of 3:1. Apart from the above differences, the operation steps for preparing diaphragm tape in this embodiment are strictly consistent with those in Example 1.
[0057] Comparative Example 1 This comparative example prepares diaphragm tape using the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that no polyolefin coating is used. Apart from the above differences, the operation steps for preparing diaphragm tape in this comparative example are strictly consistent with those in Example 1.
[0058] Comparative Example 2 This comparative example prepares diaphragm tape using the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that this comparative example uses PVDF emulsion (Arkema LBG) instead of the polyolefin emulsion in Example 1. Apart from the above differences, the operation steps for preparing diaphragm tape in this comparative example are strictly consistent with those in Example 1.
[0059] Comparative Example 3 This comparative example prepares diaphragm tape using the formulation and method provided in Example 1. The difference between this comparative example and Example 1 is that Huzhou Lvtian acrylic adhesive (LT-3056) is used instead of the acrylate polymer used in Example 1 to prepare the adhesive layer. Apart from the above differences, the operation steps for preparing diaphragm tape in this comparative example are strictly consistent with those in Example 1.
[0060] Test case 1. Test Object In this test example, the test objects include the diaphragm tapes prepared in Examples 1-7 and Comparative Examples 1-3 before and after immersion in the electrolyte. The diaphragm tapes were immersed in an electrolyte at 85°C for 4 hours, then removed, the surface droplets were wiped off, and the tapes were dried to obtain the test samples after immersion in the electrolyte. The electrolyte consisted of an organic solvent and lithium hexafluorophosphate. The organic solvent was formed by mixing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a mass ratio of 1:1:1. The concentration of lithium hexafluorophosphate in the electrolyte was 1 mol / L.
[0061] 2. Testing Methods (1) Air permeability: The test was conducted in accordance with the requirements of GB / T36363-2018. A 600mm × 100mm test object was cut as the test sample. Using a Wangyan-type air permeability meter (Asahi Seiko Co., Ltd., EG01-55-1MR), the air permeability of the test sample was measured at any position at 100mm intervals along the 600mm MD direction. The average value of the test data from 5 points was calculated and recorded as the air permeability of the test object. For the sample after soaking in electrolyte, it was first soaked in DMC, then dried before testing.
[0062] (2) Peel strength: Referring to the test method in GB / T 2792-2014 Test method for peel strength of adhesive tape, the test object was cut into a size of 24mm*150mm as the test sample. The adhesive layer was attached to the steel plate and rolled back and forth three times with a 2kg rubber roller. It was placed in an environment of 23±1℃ and 50±5%RH for 20 minutes. Then, the test sample was peeled from the steel plate at a peel speed of 300mm / min and a peel angle of 180°, and the peel strength of the test sample was recorded.
[0063] 3. Test Results and Analysis The test results for this test example are shown in Table 5. Data from Examples 1-7 and Comparative Examples 1-3 demonstrate that the present invention, by selecting an acrylate polymer with a specific molecular structure design and combining it with a polyolefin coating, can significantly improve the bonding strength and interfacial stability of the diaphragm tape in the electrolyte. Specifically, comparing the data from Example 1 and Comparative Example 1 shows that when no polyolefin coating is provided in the diaphragm tape, the acrylate polymer easily penetrates into the base film layer, leading to a reduction in the adhesive layer thickness, which in turn significantly reduces the peel strength of the diaphragm tape after immersion in the electrolyte. Furthermore, comparing Example 1 and Comparative Example 2 reveals that the adhesive layer provided by the present invention, when combined with the functional layer made from PVDF emulsion used in the prior art, exhibits debonding even without immersion in the electrolyte. This is due to the poor adhesion between the PVDF layer and the base film layer. The data from Comparative Example 3 demonstrates that, compared to the acrylate polymer diaphragm tapes with specific molecular structure designs provided in Examples 1-7 of this invention, the use of ordinary acrylate directly composited with the polyolefin coating results in poor interfacial compatibility, causing the diaphragm tapes to detach after immersion in the electrolyte.
[0064] Furthermore, based on the data from Examples 1-3, it is evident that optimizing the area of the adhesive layer in the diaphragm tape relative to the total area of the functional layers not only helps improve the permeability of the diaphragm tape but also enhances the adhesion of the adhesive layer to the functional layers. When the area of the adhesive layer relative to the total area of the functional layers is low (below 15%), the small contact area of the adhesive layer can easily lead to a decrease in the stable adhesion of the diaphragm tape. When the area of the adhesive layer relative to the total area of the functional layers is high (above 35%), although the air permeability is improved to some extent, the effect on improving the peel strength is not significant.
[0065] Furthermore, based on the data from Examples 1 and 4-6, it is evident that by optimizing the glass transition temperatures of the soft monomers, hard monomers, and functional monomers, the resulting acrylate polymer adhesive layer can maintain appropriate flexibility while possessing good cohesive strength and interfacial affinity. This design helps improve the compatibility and adhesion between the adhesive layer and the polyolefin coating, thereby enhancing the overall peel strength of the tape. Simultaneously, the adhesive layer promotes the wetting and uniform distribution of the electrolyte on its surface, which is beneficial for ion migration during cycling. Moreover, the combination of soft monomers, hard monomers, and functional monomers that meet specific glass transition temperatures also helps maintain adequate permeability of the adhesive layer during the composite process and supports the tape's structural strength performance, ultimately contributing positively to the cycle safety and stability of the battery.
[0066] Data from Examples 1 and 7 show that blending maleic anhydride-grafted polypropylene and maleic anhydride-grafted SEBS in a mass ratio of 1 to 4:1 to prepare polyolefin resin helps to achieve a balance between rigid support and flexible compatibility in the modified polyolefin resin, thereby further improving the interfacial bonding between the polyolefin coating and the acrylate adhesive layer, and also has a certain effect on improving the heat resistance of the diaphragm tape.
[0067] Table 5. Test Results
[0068] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A diaphragm tape, characterized in that, The diaphragm tape includes a functional layer and an adhesive layer; the functional layer includes a polyolefin coating, and the adhesive layer is disposed on the surface of the polyolefin coating. The adhesive layer comprises an acrylate polymer, the structural formula of which is shown in formula (I); Equation (I) In formula (I), R1 is at least one of methyl, ethyl, butyl, isooctyl, isononyl, and lauryl; R2 is at least one of methyl, ethyl, butyl, and isobutyl; R3 and R4 are hydrogen atoms and / or methyl; R5 is a substituted ethyl or propyl group; and a≥1, b≥1, c≥0, d≥1, e≥1; The number-average molecular weight of the acrylate polymer is 100,000 g / mol to 150,000 g / mol.
2. The diaphragm tape as described in claim 1, characterized in that, The area of the adhesive layer accounts for 15% to 35% of the total area of the functional layer.
3. The diaphragm tape as described in claim 1, characterized in that, The air permeability of the functional layer is 10 s / 100cc to 350 s / 100cc.
4. The diaphragm tape as described in claim 1, characterized in that, The raw materials for preparing the acrylate polymer include soft monomers, hard monomers, and functional monomers; The glass transition temperature of the homopolymer of the soft monomer is T. g1 T g1 ≤ 10℃; The glass transition temperature of the homopolymer of the hard monomer is T. g2 T g2 ≥ 20℃; The homopolymer of the functional monomer has a glass transition temperature of T. g3 -20℃≤ T g3 ≤ 140℃.
5. The diaphragm tape as described in claim 4, characterized in that, Based on the mass ratio, the ratio of soft monomer to hard monomer to functional monomer is 50~70:13~40:10~17.
6. The diaphragm tape as described in claim 4, characterized in that, Both soft and hard monomers are acrylate monomers, and functional monomers include acrylic monomers and hydroxyl-containing acrylate monomers.
7. The diaphragm tape as described in claim 1, characterized in that, The polyolefin coating is obtained by drying a polyolefin emulsion; the polyolefin emulsion is prepared by solution emulsification or melt emulsification.
8. The diaphragm tape as described in claim 7, characterized in that, The polyolefin emulsion includes a modified polyolefin resin, which is prepared by reacting a polyolefin with a modifier. The polyolefin includes at least one of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, hydrogenated styrene-ethylene-propylene-styrene block copolymer, polypropylene, polyethylene, and ethylene-vinyl acetate copolymer. The modifier includes at least one of maleic anhydride, acrylic acid, and acrylate.
9. The diaphragm tape according to any one of claims 1 to 8, characterized in that, The modified polyolefin resin is a blend of maleic anhydride-grafted polypropylene and maleic anhydride-grafted SEBS, with a mass ratio of maleic anhydride-grafted polypropylene to maleic anhydride-grafted SEBS of 1 to 4:
1.
10. A method for preparing a diaphragm tape as described in any one of claims 1 to 9, characterized in that, The preparation method includes the following steps: S1. Prepare the functional layer and adhesive layer separately: Apply acrylate polymer adhesive to the surface of the release film and dry it to obtain the adhesive layer; apply polyolefin emulsion to the surface of the base film layer and dry it to obtain the functional layer. S2. After the adhesive layer is bonded to the polyolefin coating surface of the functional layer, it is cured at high temperature to obtain the diaphragm tape.